Structural bioinformatics of membrane proteins - Frishman, Dmitrij (Springer, 2010)
With a focus on membrane proteins from the perspective of bioinformatics, this book covers a broad spectrum of topics in evolution, structure, function and bioinformatics of membrane proteins focusing on the most recent experimental results.